Management Science in Marketing: Prehistory, Origin and Early Years of the Informs Marketing College - Montgomery, David B. (Institutional Knowledge at Singapore Management University, 2001)
It is now nearly 50 years since the Institute of Management Science was founded and the prestigious journal, Management Science, began publication in October of 1954. During its first 6 years of publication of Management Science, marketing was most conspicuous by its relative absence. By the 1960s things began to accelerate, both in relation to research publication in Management Science and in marketing's share of research attention in the journal.